Optimizing electronic state in Sr2Co2O5-x with ferromagnetic state by improving oxygen vacancies for oxygen evolution reaction. (22nd May 2022) - Zhang, Qian; Sun, Maosong; Zhu, Jie; Yang, Sudong; Chen, Lin; Yang, Xulin; Wang, Pan; Li, Kui; Zhao, Peng
Abstract: The eg occupancy in perovskite oxides plays a crucial role for the oxygen electrocatalysis. Herein, we demonstrated a new method to optimize the eg filling and electronic-state of Co ions in Sr2 Co2 O5-x (SCO) via altering concentrations of oxygen vacancies using the CaH2 as reductant in an evacuated (≈10 −2  Pa) pyrex tube. As the oxygen vacancies concentration increased, the eg electron filling of SCO was optimized and its conductivity was greatly improved. Notably, the electronic state of SCO changed from antiferromagnetic (AFM) to ferromagnetic (FM) state. Moreover, the SCO exhibited a remarkable activity toward oxygen evolution reaction (OER), with a low overpotential of 320 mV and a tafel slope of 65 mV dec −1, which is superior to most well-known perovskite oxides catalysts. The theoretical calculations demonstrated that oxygen vacancies could reduce the energy barrier of OER process. This work not only establishes a clear relationship among oxygen vacancies, eg filling, magnetic behavior and OER performance, but also provides a new method for designing highly activity efficient catalysts for OER. Graphical abstract: Image 1 Highlights: New Strategy to creat oxygen vacancies and optimize Eg filling of Sr2 Co2 O5 for electrocatalyst. The electronic state of Sr2 Co2 O5-x changed from antiferromagnetic to ferromagnetic state. Sr2 Co2 O5-x indicated low overpotential and tafel slope. Oxygen vacancies concentration reduced the energy barrier of OER process.